Pengembangan Lembar Kerja Siswa (LKS) untuk Meningkatkan Kemampuan Literasi Energi Siswa SMA - Mohammad Abdul Aziz; Sri Astutik; Rayendra Wahu Bachtiar (International Consortium of Education and Culture Research Studies, 2018)
The results of the PISA (Program for International Student Assessment) research in 2015 have shown that Indonesian students' learning outcomes in the field of reading literacy are still low. The ability of Indonesian students in the field of reading literacy of Indonesian students is ranked 65th with a value of 397. The development of technology has shifted some of the culture of Indonesian society, especially youth and students, from the traditional society to semi-modern society. The shift can be seen for example in the understanding and in the use of uncontrolled energy. Therefore, the authors develop teaching materials in the form of LKS literacy energy (Student Worksheet) which integrated the energy material in physics learning which later can be used in physics learning activities in high school. The design of LKS literacy energy learning is directed to increase the energy literacy of learners which includes context, knowledge, ability, and attitude. This study is a study followed up with product design, design validation, design trials, design revisions, application of certain clusters until they can be enforced in bulk. If implemented consistently, in the long run, we can expect the concept of energy in physics can contribute to the birth of Indonesians who have energy literacy as a pattern of life and culture in people's lives.